The Comparative Analysis of the Ruminal Bacterial Population in Reindeer ( Rangifer tarandus L.) from the Russian Arctic Zone: Regional and Seasonal Effects - Larisa A. Ilina; Valentina A. Filippova; Evgeni A. Brazhnik; Andrey V. Dubrovin; Elena A. Yildirim; Timur P. Dunyashev; Georgiy Y. Laptev; Natalia I. Novikova; Dmitriy V. Sobolev; Aleksandr A. Yuzhakov; Kasim A. Laishev (Animals, 2021)
The reindeer (Rangifer tarandus L.) is a unique animal inhabitant of arctic regions. Low ambient temperatures and scant diets (primarily, lichens) have resulted in different evolutional adaptations, including the composition of the ruminal microbiota. In the study presented here, the effects of seasonal and regional aspects of the composition of the ruminal microbiota in reindeer (Nenets breed, 38 animals) were studied (wooded tundra from the Yamalo-Nenetski Autonomous District (YNAD) vs. from the Nenetski Autonomous District (NAD)). The ruminal content of calves (n = 12) and adult animals (n = 26, 15 males and 11 females) was sampled in the summer (n = 16) and winter seasons (n = 22). The composition of the ruminal microbial population was determined by the V3-V4 16S rRNA gene region sequencing. It was found that the population was dominated by Bacteroidetes and Firmicutes phyla, followed by Spirochaetes and Verrucomicrobia. An analysis of the community using non-metric multidimensional scaling and Bray–Curtis similarity metrics provided evidence that the most influential factors affecting the composition of ruminal microbiota are the region (p = 0.001) and season (p = 0.001); heat map analysis revealed several communities that are strongly affected by these two factors. In the summer season, the following communities were significantly larger compared to in the winter season: Coriobactriaceae, Erysipelothrihaceae, and Mycoplasmataceae. The following communities were significantly larger in the winter season compared to in summer: Paraprevotellaceae, Butyrivibrio spp., Succiniclasticum spp., Coprococcus spp., Ruminococcus spp., and Pseudobutyrivibrio spp. In NAD (tundra), the following communities were significantly larger in comparison to YNAD (wooded tundra): Verrucomicrobia (Verruco-5), Anaerolinaceae, PeHg47 Planctomycetes, cellulolytic Lachnospiraceae, and Succiniclasticum spp. The following bacterial groups were significantly larger in YNAD in comparison to NAD: cellulolytic Ruminococaceae, ...